2014
DOI: 10.1109/jstqe.2013.2278073
|View full text |Cite
|
Sign up to set email alerts
|

Label-Free Optical Imaging of Lymphatic Vessels Within Tissue Beds IN VIVO

Abstract: Lymphatic vessels are a part of circulatory system in vertebrates that maintain tissue fluid homeostasis and drain excess fluid and large cells that cannot easily find their way back into venous system. Due to the lack of non-invasive monitoring tools, lymphatic vessels are known as forgotten circulation. However, lymphatic system plays an important role in diseases such as cancer and inflammatory conditions. In this paper, we start to briefly review the current existing methods for imaging lymphatic vessels, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
20
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 77 publications
0
20
0
Order By: Relevance
“…As we know that the main role of vasculature system is to delivery oxygen, nutrition, fluid and signaling molecules required by living tissue, and the lymphatic system usually developed in parallel to the blood vessels in the skin [69]. Kalchenko et al showed that the combined application of LSCI and fluorescence intravital microscopy approaches provided synchronic in vivo images of blood vessels and lymph vessels [70].…”
Section: Discussionmentioning
confidence: 99%
“…As we know that the main role of vasculature system is to delivery oxygen, nutrition, fluid and signaling molecules required by living tissue, and the lymphatic system usually developed in parallel to the blood vessels in the skin [69]. Kalchenko et al showed that the combined application of LSCI and fluorescence intravital microscopy approaches provided synchronic in vivo images of blood vessels and lymph vessels [70].…”
Section: Discussionmentioning
confidence: 99%
“…The origin of these reduced-scattering connected tubular structures in the skin has been already confirmed by intradermal injection of Evan's blue dye and monitoring the uptake path by surrounding lymph vessels into the sentinel lymph node. 23 Therefore, these lymph vessels can be visualized by a proper segmentation algorithm on OCT structure images. The details of our segmentation algorithm were previously published 24 and here, we will briefly explain the process.…”
Section: Segmentation Of Lymphatic Vesselsmentioning
confidence: 99%
“…These studies in swine displayed the capability of the method to measure average velocity of tagged packets of ICG, but no spatially resolved information can be obtained, rendering the method unsuitable for accurately resolving the flow field in lymphatic vessels. Other noninvasive in vivo lymphangiography methods have been developed using an optical coherence tomography (OCT) approach or optical microangiography, a variant of OCT. 22,23 OCT lymphangiography allows for labelfree demarcation of lymphatic vessels and flow visualization. No quantitative information on flow in lymphatics was reported in these studies.…”
Section: Introductionmentioning
confidence: 99%